Sulfonic-Acid-Functionalized Silica: An Efficient, Heterogeneous and Reusable Catalyst for the Synthesis of 8-Aryl-7,8-dihydro-[1,3]dioxolo [4,5-g]chromen-6-ones - Li, Weilin; Wu, Liqiang; Yan, Fulin (Asian Journal of Chemistry, 2011)
Sulfonic-acid-functionalized silica was used as an efficient and recyclable catalyst for the onepot synthesis of 8-aryl-7,8-dihydro-[1,3]dioxolo[4,5-g]chromen-6-ones with the help of 3,4- methylenedioxyphenol, aldehydes and Meldrums' acid. Different types of aromatic aldehydes are used in the reaction and in all cases the products were obtained in good to excellent yields.